The B-Cell Follicle in HIV Infection: Barrier to a Cure - Bronnimann, Matthew P.; Skinner, Pamela J.; Connick, Elizabeth (Frontiers in Immunology, 2018)
The majority of HIV replication occurs in secondary lymphoid organs (SLOs) such as the spleen, lymph nodes, and gut associated lymphoid tissue. Within SLOs, HIV RNA+ cells are concentrated in the B-cell follicle during chronic untreated infection, and emerging data suggest that they are a major source of replication in treated disease as well. The concentration of HIV RNA+ cells in the B-cell follicle is mediated by several factors. Follicular CD4+ T-cell subsets including T-follicular helper cells and T-follicular regulatory cells are significantly more permissive to HIV than extrafollicular subsets. The B cell follicle also contains a large reservoir of extracellular HIV virions which accumulate on the surface of follicular dendritic cells (FDCs) in germinal centers. FDC bound HIV virions remain infectious even in the presence of neutralizing antibodies and can persist for months or even years. Moreover, the B-cell follicle is semi-immune privileged from CTL control. Frequencies of HIV- and SIV-specific CTL are lower in B-cell follicles compared to extrafollicular regions as the majority of CTL do not express the follicular homing receptor CXCR5. Additionally, CTL in the B-cell follicle may be less functional than extrafollicular CTL as many exhibit the recently described CD8 T follicular regulatory phenotype. Other factors may also contribute to the follicular concentration of HIV RNA+ cells. Notably, the contribution of NK cells and γδ T cells to control and/or persistence of HIV RNA+ cells in secondary lymphoid tissue remains poorly characterized. As HIV research moves increasingly towards the development of cure strategies, a greater understanding of the barriers to control of HIV infection in B-cell follicles is critical. Although no strategy has as of yet proven to be effective, a range of novel therapies to address these barriers are currently being investigated including genetically engineered CTL or CAR T cells that express the follicular homing molecule CXCR5, treatment with IL-15 or an IL-15 superagonist, use of bispecific antibodies to harness the killing power of the follicular CD8+ T cell population, and disruption of the follicle through treatments such as rituximab.